2022
DOI: 10.1161/circep.122.010850
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning–Enabled Multimodal Fusion of Intra-Atrial and Body Surface Signals in Prediction of Atrial Fibrillation Ablation Outcomes

Abstract: BACKGROUND: Machine learning is a promising approach to personalize atrial fibrillation management strategies for patients after catheter ablation. Prior atrial fibrillation ablation outcome prediction studies applied classical machine learning methods to hand-crafted clinical scores, and none have leveraged intracardiac electrograms or 12-lead surface electrocardiograms for outcome prediction. We hypothesized that (1) machine learning models trained on electrograms or ECG signals can perform bette… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Attia and colleagues have shown that AI can accurately identify patients with a history of AF from their EKGs obtained in normal sinus rhythm (20). Similarly, Tang et al also demonstrated that EKGs obtained in sinus rhythm analyzed with AI can accurately predict patients who would have favorable outcomes following AF ablation (23). These studies suggest potential signatures of rhythm disorders such as AF in EKGs obtained in normal sinus rhythm, that are not apparent and easily analyzable by traditional signal processing and statistical methods.…”
Section: Ai Applications In Predicting Drug-induced Arrhythmiamentioning
confidence: 99%
“…Attia and colleagues have shown that AI can accurately identify patients with a history of AF from their EKGs obtained in normal sinus rhythm (20). Similarly, Tang et al also demonstrated that EKGs obtained in sinus rhythm analyzed with AI can accurately predict patients who would have favorable outcomes following AF ablation (23). These studies suggest potential signatures of rhythm disorders such as AF in EKGs obtained in normal sinus rhythm, that are not apparent and easily analyzable by traditional signal processing and statistical methods.…”
Section: Ai Applications In Predicting Drug-induced Arrhythmiamentioning
confidence: 99%
“…In addition to nuanced definitions of HF beyond conventional classification of HF with reduced EF and HF with preserved EF, AI/ML-based phenotypes are increasingly reported to integrate multimodal data to identify patients at risk for adverse outcomes from HF, 138 at heightened risk for sudden cardiac arrest, 16,141 or with AF who are more likely to respond to ablation. 142,143 Challenges in Applying AI/ML in EHR EHR data are only as good as their curation and consistency. Raw EHR data are extracted from different information systems and must be linked and prepared for analysis by individuals familiar with local practice patterns (Table 6).…”
Section: Disease Classificationmentioning
confidence: 99%
“…48 ML algorithms have also been tested to predict the success of catheter ablation procedures using intracardiac EGM and a composite of EGM, ECG and clinical features in a fusion model with strong performance (AUC approaching 0.86). 49 It is clear the novel application of neural networks into electrophysiological practice may complement and enhance patient care at the treatment/ interventional level.…”
Section: Artificial Intelligence For Af Using Intracardiac Signalsmentioning
confidence: 99%